The New “Nasty Party”? Labour and the Issue of Culture in the 2019 General Election - Alma-Pierre Bonnet (Revue Française de Civilisation Britannique)
When Theresa May claimed that the Conservative Party was dubbed the “Nasty Party” in October 2002, few were those who could have contradicted her. It had suffered a second landslide defeat and its image and reputation had been damaged by the violence of the Thatcher years and tainted by accusations of racism. Seventeen years later, after Corbyn’s historic defeat in the 2019 general election, it seems that the tables have turned. Labour’s failure to bring its social(ist) message home during the so-called “once in a lifetime” election might be the climax of a decade in the wilderness. In this paper, we posit that Labour’s defeat can, in part, be explained by its incapacity to deal with one new defining element of British politics, the issue of culture. Labour willingly ignored the cultural dimension of the 2019 general election and instead, decided to focus on traditional economic policies that further alienated its traditional supporters. The first part will be devoted to the importance of culture in the 2019 general election and focus on a recent paradigm shift whereby culture is now essential in Western politics. The second part will deal with Labour’s cultural conundrum, that is, their inability to acknowledge the new cultural reality.